1999
DOI: 10.1046/j.1365-2648.1999.01198.x
|View full text |Cite
|
Sign up to set email alerts
|

Providers’ and consumers’ perspective of nurses’ caring behaviours

Abstract: The primary purpose of this article is to discuss the development and testing of a scale designed to examine nurses' caring behaviours. A pilot study was conducted with a convenience sample (n = 81) of 42 nurses (providers) and 39 patients (consumers). The setting was two community hospitals in the New England Region. The respondents were able to assign a rank of the items (nurses' caring behaviours) with a spread of mean values from 3.5 to 16.7. There was agreement on the most caring behaviour, 'The nurses tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 27 publications
1
31
0
3
Order By: Relevance
“…Increasingly, research is identifying other benefits, including increased knowledge and awareness of possible solutions to clinical problems, increased confidence, reduced emotional strain and burnout, increased participation in reflective practice,38,39 and better self-awareness 33,40. The benefits identified have implications not only for practitioners but also for patient care and employing organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, research is identifying other benefits, including increased knowledge and awareness of possible solutions to clinical problems, increased confidence, reduced emotional strain and burnout, increased participation in reflective practice,38,39 and better self-awareness 33,40. The benefits identified have implications not only for practitioners but also for patient care and employing organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Una de las habilidades es el cuidado individualizado encaminado a conocer las necesidades, experiencias, comportamientos y percepciones del paciente; a reconocer su unicidad y la de su familia (37,38,39,40,41,42), y una responsabilidad con la calidad de su práctica por las acciones que llevan a cabo, las que delega y por el mantenimiento de los estándares de la práctica de enfermería (43).…”
Section: Resultsunclassified
“…Walsh and Dolan (1999), while exploring emergency nurses' perception of care, showed that nurses in accident and emergency departments scored lower in the psychosocial and holistic dimensions of care than general nurses (13). Other studies have also reported differences between nurses' and patients' perceptions of care (14,15).…”
Section: Introductionmentioning
confidence: 99%